Immediate versus delayed induction of labour in hypertensive disorders of pregnancy: a systematic review and meta-analysis - Jia Li; Xuecheng Shao; Shurong Song; Qian Liang; Yang Liu; Xiaojin Qi (BMC, 2020)
Abstract Background Mothers with hypertensive disorder of pregnancy can be managed with either immediate or delayed induction of labour with expectant monitoring of both mother and baby. There are risks and benefits associated with both the type of interventions. Hence, this review was conducted to compare outcomes of immediate and delayed induction of labour among women with hypertensive disorder of pregnancy based on disease severity and gestational age. Methods We conducted systematic searches in various databases including Medline, Cochrane Controlled Register of Trials (CENTRAL), Scopus, and Embase from inception until October 2019.Cochrane risk of bias tool was used to assess the quality of published trials. A meta-analysis was performed with random-effects model and reported pooled Risk ratios (RR) with 95% confidence intervals (CIs). Results Fourteen randomized controlled trials with 4244 participants were included. Majority of the studies had low or unclear bias risks. Amongst late onset mild pre-eclampsia patients, the risk of renal failure was significantly lower with immediate induction of labour (pooled RR: 0.36; 95%CI: 0.14 to 0.92). In severe pre-eclampsia patients, immediate induction of labour significantly reduced the risk of having small-for-gestational age babies compared to delayed induction of labour (pooled RR: 0.49; 95%CI: 0.29-0.84).Delayed induction was found to significantly reduce the risk of neonatal respiratory distress syndrome risk among late onset mild pre-eclampsia patients (pooled RR: 2.15; 95%CI: 1.14 to 4.06) None of the other outcomes demonstrated statistically significant difference between the two interventions. Conclusion Delayed induction of labour with expectant monitoring may not be inferior to immediate induction of labour in terms of neonatal and maternal outcomes. Expectant approach of management for late onset mild pre-eclampsia patients may be associated with decreased risk of neonatal respiratory distress syndrome, while immediate induction of labour among severe pre-eclampsia patients is associated with reduced risk of small-for-gestational age babies and among mild pre-eclampsia patients, it is associated with reduced risk of severe renal impairment.